Memaknai Ulang Wacana Waria dalam Konteks Indonesia (Analisis Hermeneutika Terhadap Novel “Perempuan Tanpa V”) - Muhammad Syafi’i (Refleksi: Jurnal Filsafat dan Pemikiran Keislaman, 2018)
The social construction of transvestites which has so far been still far from what is expected, transgenders in general often get stereotypes that have long taken root so that they become individuals/groups who are marginalized in society. They tend to be shunned because religion and morality are big questions due to their tendency to like same-sex. This  construction is entrenched and to this day, they have not received a proper place and are made as human beings as usual. Related to this, there is a novel called "Perempuan Tanpa V" which tells of transvestites in different perspectives. Because of that the writer wants to study this novel and further find out the construction of transvestites he wants to convey. This study uses Gadamer's hermeneutics approach as an analysis knife. The definition of transvestites in this novel  eventually leads to the construction of transvestites who are built more positively, are not discriminatory, and try to break the stereotype of transvestites that has been understood by the community: irregularities and immorality.